Development Of The System Of Verification Proceedings In The Criminal Process Of The Republic Of Uzbekistan (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article is devoted to the modern system of verification proceedings in the criminal process of the Republic of Uzbekistan from 1984 to the present. For each historical stage, the most significant features characterizing the instantiation relationship and the main features of verification proceedings are formulated. In conclusion, proposals are made for further improvement of the system of modern verification proceedings, based on trends in the development of criminal procedural legislation